2019
DOI: 10.1128/aem.02474-18
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Mobile Denitrification Genes Identified in Azospirillum sp. Strain TSH58

Abstract: Denitrification ability is sporadically distributed among diverse bacteria, archaea, and fungi. In addition, disagreement has been found between denitrification gene phylogenies and the 16S rRNA gene phylogeny. These facts have suggested potential occurrences of horizontal gene transfer (HGT) for the denitrification genes. However, evidence of HGT has not been clearly presented thus far. In this study, we identified the sequences and the localization of the nitrite reductase genes in the genomes of 41 denitrif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Magnetospirillum contains genes capable of compiling nitrate reductase, nitrite reductase, nitric oxide reductase, and nitrous oxide reductase, with complete denitrification capability [ 82 ]. Azospirillum has complete denitrification functional genes and can fix nitrogen [ 83 , 84 ]. In the A48 treatment, the dominant bacteria (relative abundance > 3%) were Pseudomonas (61.34%), Diaphorobacter (9.54%), and Lysobacter (4.09%).…”
Section: Resultsmentioning
confidence: 99%
“…Magnetospirillum contains genes capable of compiling nitrate reductase, nitrite reductase, nitric oxide reductase, and nitrous oxide reductase, with complete denitrification capability [ 82 ]. Azospirillum has complete denitrification functional genes and can fix nitrogen [ 83 , 84 ]. In the A48 treatment, the dominant bacteria (relative abundance > 3%) were Pseudomonas (61.34%), Diaphorobacter (9.54%), and Lysobacter (4.09%).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that Azospirillum spp. not only have nitrogen-fixing function, but also have some other functions, such as heavy oil degrading, atrazine degrading, denitrification ability, carotenoids produce ( Jang et al, 2019 ; Liu et al, 2019 ; Wu et al, 2020 ; Mishra et al, 2021 ), and the functional diversity of Azospirillum spp. needs to be studied future.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this study, association of denitrification genes ( nir ‐ nor cluster) on a composite transposon was recently reported in an Azospirillum sp. denitrifier (Jang et al 2019b). These results suggest that denitrification genes might be horizontally transferred among cells.…”
Section: Discussionmentioning
confidence: 99%